Exploring teachers’ views on how educational methodologies foster social innovation competencies - Isusi-Fagoaga, Rosa; Planells-Aleixandre, Ester; García-Aracil, Adela (Frontiers in Education, 2026)
This paper highlights the role of higher education institutions in promoting the competencies required for students to engage with complex societal and professional environments. Embedding social innovation competencies into the educational experience enables universities not only to prepare graduates for the labor market but also to equip them to act as agents of change, contributing to societal transformations. To gain insights into which teaching-learning approaches should be used in higher education study programs to promote the appropriate social innovation competencies, the ‘Spanish Universities Involvement in Social Innovation Activities’ SUISIA data, collected during the academic year 2021/2022, is used. The findings highlight that the most effective development of social innovation competencies associated with organizational, entrepreneurial, collaborative, and resilience-related competencies arises from a balanced pedagogical approach, integrating student-centered methods with the structured guidance provided by teacher-centered instruction. The complementary interaction between methodologies such as design thinking, cooperative learning, gamification, oral presentations, and the teacher as the main source of information reinforces that students benefit from participatory learning without losing the conceptual coherence and experience that instructors provide. By promoting this combined pedagogical model and reducing disciplinary disparities in competency development, higher education institutions can better align their educational mission with the imperatives of sustainable development and social equity.